VARIATIONS IN THE CHROME SPINEL CHEMISTRY OF A SERPENTINIZED MANTLE SECTION, KEMPERSAI MASSIF, KAZAKHSTAN - Kussainov, Aldiyar (Nazarbayev University School of Mining and Geosciences, 2024)
Cr-spinel, which occurs in a variety of rocks, can serve as a valuable indicator of geological processes and formation conditions. This study focuses on the three serpentinite samples, collected from the Khromtau region, Aktobe which is geologically a part of the Kempirsai massif of southern Urals. All three samples, namely AK-3, AK-4 and AK-6, contain minerals such as olivine, serpentine and chrome spinel, in varying abundance.The mineral chemistry of the chrome spinels obtained using SEM EDS technique yielded similar composition (MgO=9-11.5%; FeO= 22-23%; Cr2O3=54-59%; Al2O3=9.5-12%) except for sample AK-3, which has an increased amount of magnesium (MgO=12.5%) and aluminum (20.95%), indicating that the sample crystallized from a slightly modified magma. However, the presence of olivine with high Mg content (Fo#=0.88-0.92) in all three samples and low magnesium in the chrome spinels in samples AK-4 and AK-6 indicate that spinel samples are almost co-crystallized with olivine. It can be therefore be concluded that serpentinization has not much altered the chrome spinel chemistry and hence can be a potential indicator of the tectonic setting. With the use of various tectonic discrimination diagrams, it can be concluded that these samples belong to supra subduction zone peridotites formed in a volcanic arc environment.
Keywords: Research Subject Categories::NATURAL SCIENCES; Chromite; Chrome spinel; Serpentinite; Type of access: Restricted